2018
DOI: 10.1093/aobpla/ply003
|View full text |Cite
|
Sign up to set email alerts
|

Warming increases the sensitivity of seedling growth capacity to rainfall in six temperate deciduous tree species

Abstract: Using a fully factorial precipitation by warming experiment in an old-field ecosystem in the northeastern USA we studied the climatic sensitivity of seedlings of six native tree species. Warm and dry conditions suppressed seedling growth, but affected species differently by increasing mortality, enhancing rates of herbivory or decreasing foliar carbon uptake. Our results indicate that, in the northeastern USA, dry years in a future warmer environment could have damaging effects on the growth capacity of early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…The two studies that simultaneously examined CO 2 and temperature found no interactive effect on feeding damage (Johns et al ., 2003; Himanen et al ., 2009). Yet, temperature and drought interacted to augment herbivre damage on St John's wort flowers (Fox et al ., 1999) and red oak leaves (Rodgers et al ., 2018). In addition, Lu et al .…”
Section: Resultsmentioning
confidence: 99%
“…The two studies that simultaneously examined CO 2 and temperature found no interactive effect on feeding damage (Johns et al ., 2003; Himanen et al ., 2009). Yet, temperature and drought interacted to augment herbivre damage on St John's wort flowers (Fox et al ., 1999) and red oak leaves (Rodgers et al ., 2018). In addition, Lu et al .…”
Section: Resultsmentioning
confidence: 99%
“…These trends are not universal, however, and many studies stress that the effects of higher temperatures are often species‐ and site‐specific. In a meta‐analysis by Rustad et al (2001), forest growth had both positive and negative responses to warming with a net response of ~0, and other studies report higher latitude tree species can experience reduced growth in higher temperatures, based on to (a) the form of the species (deciduous vs. evergreen, with evergreens more often showing negative effects; Way and Oren 2010); (b) when the species is growing near its warm range limit (Reich et al 2015); (c) when soil fertility is insufficient to support faster growth (Ryan 2013); and (d) when warming is combined with reduced precipitation (Wu et al 2011, Rodgers et al 2018). These contrasting results demonstrate the need for more study.…”
Section: Discussionmentioning
confidence: 99%
“…This research was conducted in an old‐field ecosystem at the Boston area climate experiment (BACE) site in Waltham, Massachusetts (42°23′N, 71°13′W). The species composition at the site consists of a mix of native and introduced annual, biennial and perennial grasses and forbs, and planted native tree seedlings (Hoeppner & Dukes, 2012; Rodgers et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The three resource supply treatment levels were: ambient rainfall (‘ambient’), 50% reduced rainfall (‘drought’) and 50% increased rainfall (‘wet’). Precipitation treatments at the BACE site are achieved using partial rainout shelters (established in 2007) that collect half of the precipitation over the drought treatments and immediately deliver it to the wet treatments via pumps and a sprinkler system (Figure ; see Hoeppner & Dukes, 2012; Rodgers et al, 2018 for more information about the BACE site). In total, we used 36 plots (3 treatments × 3 shelters × 4 replicates), each 2 m × 2 m, within which we established smaller sampling plots (see below).…”
Section: Methodsmentioning
confidence: 99%